Pengaruh WACC terhadap Nilai Perusahaan (Studi Kasus pada PT. Hanjaya Mandala Sampoerna Tbk. dan PT. Gudang Garam Tbk.) - M. Nur Rizqi (Jurnal Ilmiah Binaniaga, 2010)
The company requires funds that derived to debt, and own capital. Sources of funds  used by company must be able to increase the value of the company. Increasing the value of the company can maximize prosperity stakeholder include stakeholders to wards the company, namely that is employees, management, creditor, supplier, communities, companies, government, and stockholder. Target of  this research is for know how influence of proportion capital structure to WACC at PT. Hanjaya Mandala Sampoerna, Tbk and PT. Gudang Garam, Tbk and for know how  much influence WACC to company value at PT. Hanjaya Mandala Sampoerna, Tbk and PT. Gudang Garam, Tbk. Analysis method used by is correlation coefficient for the relationships between the variables and coefficient determination to measure the closeness relationships between the variable and regression coefficient to measure the influence of the free variable and bound variables for the ratio analysis to know level of proportion each variable. Research Result indicates that at to test t at PT, Hanjaya Mandala Sampoerna, Tbk is capital structure proportion haves significant influence on the WACC with t calculate bigger than t tables or 3.591 bigger than 2.776 . For WACC to value of share price with t calculate bigger than t tables 3.624 bigger than 2.776 have significant influence. While PT. Gudang Garam, Tbk is capital structure proportion haves significant influence to WACC with t calculate bigger than t tables or 3.917 bigger than 2.776 . For WACC to value of share price with t calculate bigger than t tables or -1.640 not have influence that is not significant.